Innovation-Oriented HR Strategy Transformation and Business Model Reengineering: Empirical Insights from Ukrainian Agribusiness (Marketing i Menedžment Innovacij)
This article explores the ongoing scientific discourse surrounding the transformation of innovation-oriented HR strategies and the reengineering of business models in Ukrainian agricultural enterprises amid the expansion of the digital economy. Particular emphasis is placed on the application of the integral strategizing paradigm and the use of the Tereshchenko model, which enables the integration of digital, value-based, and behavioural dimensions into a unified HR business architecture. The research employs factor analysis to assess the need for business process optimization across the following indicator groups: the integral vector of enterprise resource productivity (land, labour, and capital), reflecting resource efficiency; the integrated vector of business process profitability; the integrated financial vector; and the vector of business model effectiveness. This system of composite indicators offers a holistic evaluation of the systemic efficiency of agricultural enterprises, encompassing not only operational performance but also strategic, organizational, and cultural dimensions. The proposed methodology serves as a meta-analytical framework, synthesizing the HR strategy, resource management, and innovation-driven development. The study reveals that the Tereshchenko model offers a strategic advantage for Ukrainian agribusinesses by coherently aligning the business model, organizational culture, resource use, and employee behavioural dynamics. This approach is particularly relevant in the context of post conflict recovery, digital transformation, and demographic challenges facing the sector. The study's findings support the enhancement of HR strategies in agricultural enterprises through the adoption of AI-based forecasting and workforce planning, digital recruitment tools (such as chatbots, online surveys, and digital platforms), and the implementation of HRM systems to automate human resource functions. These measures aim to align human capital with evolving business environments and facilitate the adoption of modernized business models.